Disseminating results to clinical trial participants: a qualitative review of patient understanding in a post-trial population. - Darbyshire, J; Price, H (BMJ Publishing Group, 2012)
Objective To identify the most appropriate format for results dissemination to maximise understanding of trial results. Design Qualitative Setting Of the original 58 4-T trial centres, 34 agreed to take part in this ancillary research. Participants All participants from these centres were eligible. All 343 participants were sent questionnaires. Primary and secondary outcome measures The low response rate meant that we were unable to make any firm conclusions about the patients’ preferred method of dissemination; however, we were able to comment on the level of understanding demonstrated by the trial participants. Results All 40 (12%) returned questionnaires were received from 15 centres. We received no questionnaires from over half of the centres. The questionnaires which were returned demonstrated broad satisfaction with the results letter, general enthusiasm for the trial and a variable level of understanding of the results; however, there was a high proportion of responders who were not clear on why the research was undertaken or what the results meant. Conclusions The low response rate may be related to delays during the trial set-up process suggesting that interest in a study quickly wanes for both patients and centres. From this we deduce that rapid dissemination of results is needed if it is to have any impact at all. The responders are likely to reflect a biased cohort who were both enthusiastic about the research and who had a good experience during their 3 years in the 4-T trial. It is perhaps not surprising therefore that the overview is positive. That this population was still not fully informed about the purpose of the research would seem to confirm a low level of understanding among the general public which we suggest should be addressed during the consent process